Where do golf driver swings go wrong? Factors influencing driver swing consistency - Zhang, X.; Shan, G. (Scandinavian Journal of Medicine & Science in Sports, 2014)
One of the challenging skills in golfing is the driver swing. There have been a large number of studies characterizing golf swings, yielding insightful instructions on how to swing well. As a result, achieving a sub-18 handicap is no longer the top problem for golfers. Instead, players are now most troubled by a lack of consistency during swing execution. The goal of this study was to determine how to consistently execute good golf swings. Using 3D motion capture and full-body biomechanical modeling, 22 experienced golfers were analysed. For characterizing both successful and failed swings, 19 selected parameters (13 angles, 4 time parameters, and 2 distances) were used. The results showed that 14 parameters are highly sensitive and/or prone to motor control variations. These parameters sensitized five distinct areas of swing to variation: (a) ball positioning, (b) transverse club angle, (c) transition, (d) wrist control, and (e) posture migration between takeaway and impact. Suggestions were provided for how to address these five distinct problem areas. We hope our findings on how to achieve consistency in golf swings will benefit all levels of golf pedagogy and help maintain/develop interests to involve more golf/physical activity for a healthy lifestyle.